Emerging Functions and Clinical Applications of Exosomal ncRNAs in Ovarian Cancer - Zhang, Yu; Wei, Yi-Jing; Zhang, Yi-Fei; Liu, Hao-Wen; Zhang, Yin-Feng (Frontiers in Oncology, 2021)
Ovarian cancer (OC) is one of the deadliest gynecological malignancies worldwide and has a high mortality rate. Its dismal prognosis is closely related to late diagnosis and drug resistance. Exosomes are a novel means of intercellular communication that are involved in the genesis and development of tumors by delivering a variety of biologically active molecules, including proteins, lipids, and nucleic acids. As an important component, noncoding RNAs (ncRNAs) are selectively enriched in exosomes and participate in the regulation of specific aspects of OC development, such as proliferation, invasion, metastasis, angiogenesis, immune escape, and treatment resistance. Therefore, strategies that specifically target exosomal ncRNAs may be attractive therapeutic options. Exosomes are readily available in almost all types of human biological fluids and are biocompatible, making them promising biomarkers of OC as well as targets for therapeutic applications. In this review, we briefly summarize the biology of exosomes, the function of exosomal ncRNAs in OC development, and their potential clinical applications as biomarkers and therapeutic tools. Ideally, exosomal ncRNAs will become increasingly valuable in the diagnosis and treatment of OC in the near future.